Expediente - Editorial, Equipe (Contemporanea, 2024)
PROJETO GRÁFICO Tainá Moraes e Edvaldo Monteiro DIAGRAMAÇÃO Zeta Studio EDITORES Ivanise Andrade Lívia Vieira Susana Morales EDITOR ADJUNTO André Holanda CONSELHO EDITORIAL Adriano Duarte, Universidade Nova de Lisboa, Lisboa, Portugal Afonso Albuquerque, Universidade Federal Fluminense, Niterói, Rio de Janeiro, Brasil Alessandra Aldé, Universidade do Estado do Rio de Janeiro, Rio de Janeiro - RJ, Brasil Ana Paula Goulart, Universidade Federal do Rio de Janeiro, Rio de Janeiro - RJ, Brasil André Lemos, Universidade Federal da Bahia, Brasil Andrew Herman, Wilfrid Laurier University, Ontario, Canadá Angela Prysthon, Universidade Federal de Pernambuco, Recife, Pernambuco, Brasil Antonio Fidalgo, Universidade da Beira Interior, Covilhã, Portugal Benjamim Picado, Universidade Federal Fluminense, Niterói - Brasil César Guimarães, Universidade Federal de Minas Gerais, Belo Horizonte, Brasil Christa Berger, Universidade do Vale do Rio dos Sinos, São Leopoldo, Rio Grande do Sul, Brasil Eneus Trindade, Universidade de São Paulo, São Paulo, Brasil Erick Felinto, Universidade do Estado do Rio de Janeiro, Rio de Janeiro, Brasil Evelyne Cohen, École Nationale Supérieure Sciences de l’information et des bibliothèques, Villeurbanne, França Francisco Paulo Jamil Almeida Marques, Universidade Federal do Ceará, Fortaleza, Brasil François Jost, Université Sorbonne Nouvelle-Paris 3, Paris, França Giovandro Marcus Ferreira, Universidade Federal da Bahia, Salvador, Bahia, Brasil Guilherme Maia de Jesus, Universidade Federal da Bahia, Salvador, Bahia, Brasil Iluska Coutinho, Universidade Federal de Juiz de Fora, Juiz de Fora, Minas Gerais, Brasil Itania Maria Mota Gomes, Universidade Federal da Bahia, Salvador, Bahia, Brasil James Katz, Rutgers University, New Brunswick, Estados Unidos Javier Días Noci, Universidad Pompeu Fabra, Barcelona, Espanha João Freire Filho, Universidade Federal do Rio de Janeiro, Rio de Janeiro - RJ, Brasil José Luiz Braga, Universidade do Vale do Rio dos Sinos, São Leopoldo, Rio Grande do Sul, Brasil Juremir Machado, Pontifícia Universidade Católica do Rio Grande do Sul, Porto Alegre, Brasil Kimberly Sawchuk, Concordia University, Montreal, Canadá Liv Sovik, Universidade Federal do Rio de Janeiro, Rio de Janeiro - RJ, Brasil Marcius Freire, Universidade Estadual de Campinas, Campinas, São Paulo, Brasil Marcos Silva Palacios, Universidade Federal da Bahia, Brasil Maria Ataíde Malcher, Universidade Federal do Amazonas, Manaus, Amazonas, Brasil Maria Carmem Jacob, Universidade Federal da Bahia, Salvador, Bahia, Brasil Marie-France Chambat-Houillon, Université Sorbonne Nouvelle-Paris 3, Paris, França Michel Maffesoli, Sorbonne, Paris, França Othon Jambeiro, Universidade Federal da Bahia, Brasil Pierre Lévy, Ottawa University, Ottawa, Canadá Rob Shields, University of Alberta, Edmonton, Canadá Rousiley Maia, Universidade Federal de Minas Gerais, Belo Horizonte, Minas Gerais, Brasil Will Straw, McGill Institute, Montreal, Canadá Wilson da Silva Gomes, Universidade Federal da Bahia, Salvador, Bahia, Brasil